Constrained sintering and cracking of air plasma sprayed thermal barrier coatings: experimental observation and modelling - Zhang, X; Cocks, ACF; Okajima, Y; Takeno, K; Torigoe, T (Wiley, 2021)
The development of vertical cracks in air plasma sprayed (APS) thermal barrier coatings (TBCs) during thermal cycling and constrained sintering under a temperature gradient is investigated. Microstructural analysis shows that the development of the vertical cracks is associated with multiple processes, including sintering during the hold period and cleavage during cooldown. Inspired by the experimental observations, an image‐based sintering model is used to simulate the development of vertical cracks as the coating sinters while constrained by a substrate. The computational results show that microstructural imperfections can develop into vertical cracks, which then propagate towards the interface. A simple analytical model is presented for the threshold level of in‐plane stress for the onset of propagation of a vertical crack during constrained sintering. By combining the results of these different modelling approaches, the cross‐coupling of the material and geometric parameters, and how this determines the sintering response (microstructure evolution) and vertical crack formation is evaluated. In addition, the growth of vertical cracks by a cleavage mechanism during cooldown is examined and the coupling between sintering, cleavage crack growth and TBC lifetime is explored.